A study on relationship among apoptosis rates, number of peripheral T cell subtypes and disease activity in rheumatoid arthritis. (31st October 2013) - Ji, Lanlan; Geng, Yan; Zhou, Wei; Zhang, Zhuoli
Abstract: Aim: Rheumatoid arthritis is characterized by type 17 helper T cell (Th17)/regulatory T cell (Treg) imbalance. The objective of this article is to study whether insufficient apoptosis contributes to the imbalance of Th17/Treg in rheumatoid arthritis. Methods: Twenty‐one rheumatoid arthritis patients and eight healthy volunteers were involved in this study. The percentage of CD4 + interleukin (IL)‐17 + T cells and CD4 + transcription factor‐forkhead box protein 3 (Foxp3) + T cells were measured by flow cytometry, and active caspase‐3 labeling was used to detect early apoptosis. The number of T cell subtypes in peripheral blood between the two groups was compared, as well as the apoptotic ratio. Results: Neither the number of Th17 nor Treg cells was significantly different between rheumatoid arthritis patients and healthy controls. However, the number of regulatory T cells positively correlated with erythrocyte sedimentation rate, Disease Activity Score of 28 joints and rheumatoid factor. For the apoptosis of T cell subtypes, the percentage of apoptotic Th17 cells was higher in peripheral blood of rheumatoid arthritis patients compared to controls. Furthermore, peripheral Th17 cells were more sensitive to apoptosis than Treg cells, but there was no difference between rheumatoid arthritis patients and controls. Conclusion: It seemed that there was no relationship between the number and apoptosis ratio of peripheral Th17/Treg cells. But the number of Treg cells positively correlated with disease activity. Furthermore, Th17 cells are more sensitive to apoptosis after freezing, especially in RA patients. This serendipitous finding may provide new areas for the further study of these two cell populations.